The shrinking endogeneity of optimum currency areas criteria: Evidence from the European Monetary Union—A beta regression approach - Mendonça, António (2022)
The endogeneity of optimum currency area criteria has been widely studied. Literature suggests the existence of a positive relationship between trade intensity and business cycle correlation. Using a beta regression model for the Eurozone we have concluded that trade has a decreasing marginal effect on business cycle correlation.